2015
DOI: 10.1177/1533317514568339
|View full text |Cite
|
Sign up to set email alerts
|

Living With Mild to Moderate Alzheimer Patients Increases the Caregiver’s Burden at 6 Months

Abstract: The objective of our study was to demonstrate that living with a person affected by mild to moderate Alzheimer's disease can lead to an increased perception of the caregiver's burden using the Caregiver Burden Inventory (CBI). The sample consisted of 153 dyads, caregiver-patient. At baseline, a greater perception of the caregiver's burden was observed in the live-in caregivers. A further increase in the total burden of the live-in caregivers was noticed at the 6-month follow-up. More specifically, with the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 42 publications
4
13
0
2
Order By: Relevance
“…We noted that live‐in caregivers experienced a higher social and physical burden and their level of irritation increased over time. These data confirm the results of Raccichini et al () who showed that cohabitation was associated with a higher social and emotional burden. Cohabitation involves constantly attending to the needs of the PwD, which creates a greater burden and stress.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We noted that live‐in caregivers experienced a higher social and physical burden and their level of irritation increased over time. These data confirm the results of Raccichini et al () who showed that cohabitation was associated with a higher social and emotional burden. Cohabitation involves constantly attending to the needs of the PwD, which creates a greater burden and stress.…”
Section: Discussionsupporting
confidence: 92%
“…Raccichini et al () considered that live‐in adult–child caregivers experienced the same level of burden over time. Our research supports their conclusions, because this group maintained the highest level of burden throughout the follow‐up, which was associated with poorer mental health.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations